First global report of multiple herbicide resistance in Eleusine indica biotypes from Indonesia - ARI BUDIAWAN; DENNY KURNIAIDE; UUM UMIYATI; RYAN WIDIANTO (Smujo International, 2025)
Abstract. Budiawan A, Kurniaide D, Umiyati U, Widianto R. 2025. First global report of multiple herbicide resistance in Eleusine indica biotypes from Indonesia. Asian J Agric 9: 629-635. Eleusine indica (goosegrass) is a major weed in maize cultivation and has evolved resistance to several herbicides worldwide. However, resistance to atrazine (a photosystem II inhibitor) and mesotrione (a 4-hydroxyphenylpyruvate dioxygenase inhibitor) has not previously been reported. This study aimed to verify farmer observations of reduced herbicide efficacy by screening 49 E. indica biotypes collected from six maize-producing provinces in Indonesia. A resistant biotype of the test sample was collected from maize fields following farmers' reports of lower efficacy of these herbicides. Greenhouse bioassays were conducted using atrazine (1,200 g a.i. ha-1) and mesotrione (150 g a.i. ha-1) at the 2-3 leaf stage. Resistance was classified based on plant survival three weeks after herbicide application. Screening results indicated the presence of 30 E. indica biotypes exhibiting resistance to atrazine, 13 of which demonstrated signs of developing resistance, and 6 were susceptible. For mesotrione, 4 biotypes were resistant, 2 were showing signs of resistance, and 43 were susceptible. A total of 4 biotypes originating from South Sulawesi exhibited resistance to atrazine and mesotrione in a multiple-resistant pattern. Notably, 4 biotypes from South Sulawesi exhibited multiple resistance to both herbicides. This study represents the first global report of E. indica multiple resistant to atrazine and mesotrione, particularly in Indonesia. The declining effectiveness of these key herbicides highlights the urgent need for Integrated Weed Management (IWM) strategies that combine chemical rotation, mixtures with complementary modes of action, and non-chemical practices to mitigate the further spread of resistance.